1994
DOI: 10.1002/jsfa.2740660206
|View full text |Cite
|
Sign up to set email alerts
|

Glycoalkaloid concentration of potato tubers following continuous illumination

Abstract: The total glycoalkaloid concentration of dormant (non-sprouted) and sprouted potato tubers cv Pentland Hawk was measured following 13 days continuous illumination (250 pmol m -' s-photosynthetically active radiation) using high-performance liquid chromatography. Comparisons were made of the influence of three sources of illumination : high-pressure mercury, high-pressure sodium and fluorescent tube type warm white. Glycoalkaloid concentrations in both dormant and sprouted tubers increased over 13 days illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
(5 reference statements)
5
32
0
Order By: Relevance
“…Since potatoes are inevitably exposed to light (daylight, fluorescent and incandescent) and wounding (chipping, slicing) in the processing and marketing chain, stimulation of glycoalkaloids presents a major hazard to food safety. Recent studies, however, have shown that glycoalkaloid concentrations failed to increase significantly in cv Desiree and Pentland Hawk after exposure to fluorescent-and mercury-derived radiation respectively (Percival et al 1993(Percival et al , 1994 Results 59 J Sci Food Agric 0022-5142/96/$0! ).00 Q 1996 SCI.…”
Section: Introductionmentioning
confidence: 97%
“…Since potatoes are inevitably exposed to light (daylight, fluorescent and incandescent) and wounding (chipping, slicing) in the processing and marketing chain, stimulation of glycoalkaloids presents a major hazard to food safety. Recent studies, however, have shown that glycoalkaloid concentrations failed to increase significantly in cv Desiree and Pentland Hawk after exposure to fluorescent-and mercury-derived radiation respectively (Percival et al 1993(Percival et al , 1994 Results 59 J Sci Food Agric 0022-5142/96/$0! ).00 Q 1996 SCI.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that these glycoalkaloids show acute toxicity (Jellema et al, 1980;McMillan & Thompson, 1980), chronic toxicity (Mun et al, 1975;Keeler et al, 1976), and have a bitter taste (Sinden & Deahl, 1976;Woolfe, 1987). The intrinsic glycoalkaloid content in tubers of commercial potato cultivars is low due to selection in breeding, but the content may increase in response to environmental stress conditions, such as light (Friedman, 1997;Griffiths et al, 1994;Kozukue et al, 1993;Maga, 1980;Percival & Dixon, 1994;Percival, 1999;Sinden et al, 1984;Woolfe, 1987), frost and hail damage, and wounding during harvesting or postharvest handling (Woolfe, 1987). Among these stress conditions, the stimulation of glycoalkaloid accumulation with light exposure is a major problem for farmers, packers, suppliers, and vendors of potato (Percival & Dixon, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic glycoalkaloid content in tubers of commercial potato cultivars is low due to selection in breeding, but the content may increase in response to environmental stress conditions, such as light (Friedman, 1997;Griffiths et al, 1994;Kozukue et al, 1993;Maga, 1980;Percival & Dixon, 1994;Percival, 1999;Sinden et al, 1984;Woolfe, 1987), frost and hail damage, and wounding during harvesting or postharvest handling (Woolfe, 1987). Among these stress conditions, the stimulation of glycoalkaloid accumulation with light exposure is a major problem for farmers, packers, suppliers, and vendors of potato (Percival & Dixon, 1994). This is because potato is exposed to various lights and illuminations, such as daylight, fluorescent light, and incandescent light, during harvest, transport, and marketing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of light as a positive elicitor of glycoalkaloid synthesis in potato tubers is well recognised, 11±13 further studies have shown that rates of glycoalkaloid accumulation were signi®cantly reduced in cvs Desiree and Pentland Hawk after exposure to¯uorescent and mercury light respectively. 10,14 Whether this response occurs in other genotypes remains unknown. Use of alternative light sources may offer a technique to markedly reduce glycoalkaloid synthesis in potato tubers during marketing and sale and thus improve consumer safety.…”
Section: Introductionmentioning
confidence: 95%